RECON-Dependent Inflammation in Hepatocytes Enhances Listeria monocytogenes Cell-to-Cell Spread - Adelle P. McFarland (American Society for Microbiology, 2018)
ABSTRACT The oxidoreductase RECON is a high-affinity cytosolic sensor of bacterium-derived cyclic dinucleotides (CDNs). CDN binding inhibits RECON’s enzymatic activity and subsequently promotes inflammation. In this study, we sought to characterize the effects of RECON on the infection cycle of the intracellular bacterium Listeria monocytogenes, which secretes cyclic di-AMP (c-di-AMP) into the cytosol of infected host cells. Here, we report that during infection of RECON-deficient hepatocytes, which exhibit hyperinflammatory responses, L. monocytogenes exhibits significantly enhanced cell-to-cell spread. Enhanced bacterial spread could not be attributed to alterations in PrfA or ActA, two virulence factors critical for intracellular motility and intercellular spread. Detailed microscopic analyses revealed that in the absence of RECON, L. monocytogenes actin tail lengths were significantly longer and there was a larger number of faster-moving bacteria. Complementation experiments demonstrated that the effects of RECON on L. monocytogenes spread and actin tail lengths were linked to its enzymatic activity. RECON enzyme activity suppresses NF-κB activation and is inhibited by c-di-AMP. Consistent with these previous findings, we found that augmented NF-κB activation in the absence of RECON caused enhanced L. monocytogenes cell-to-cell spread and that L. monocytogenes spread correlated with c-di-AMP secretion. Finally, we discovered that, remarkably, increased NF-κB-dependent inducible nitric oxide synthase expression and nitric oxide production were responsible for promoting L. monocytogenes cell-to-cell spread. The work presented here supports a model whereby L. monocytogenes secretion of c-di-AMP inhibits RECON’s enzymatic activity, drives augmented NF-κB activation and nitric oxide production, and ultimately enhances intercellular spread. IMPORTANCE To date, bacterial CDNs in eukaryotes are solely appreciated for their capacity to activate cytosolic sensing pathways in innate immunity. However, it remains unclear whether pathogens that actively secrete CDNs benefit from this process. Here, we provide evidence that secretion of CDNs leads to enhancement of L. monocytogenes cell-to-cell spread. This is a heretofore-unknown role of these molecules and suggests L. monocytogenes may benefit from their secretion in certain contexts. Molecular characterization revealed that, surprisingly, nitric oxide was responsible for the enhanced spread. Pathogens act to prevent nitric oxide production or, like L. monocytogenes, they have evolved to resist its direct antimicrobial effects. This study provides evidence that intracellular bacterial pathogens not only tolerate nitric oxide, which is inevitably encountered during infection, but can also capitalize on the changes this pleiotropic molecule enacts on the host cell.